Vascular and neurodegenerative cognitive impairments: a clinical case report - V. V. Zakharov; N. V. Vakhnina (Неврология, нейропсихиатрия, психосоматика)
To establish the exact cause of cognitive impairment (CI) is of great importance for appropriate patient management and disease prognosis. The paper describes a patient with moderate CI, with respect of whom both vascular and neurodegenerative pathology may be discussed. A specific example is used to consider the currently accepted approaches to the differential diagnosis of the most common nosological entities of cognitive impairment, including an analysis of its clinical neurological and neuropsychological symptoms and the results of instrumental and neuroradiological examinations. The present-day ideas on mixed (vascular and degenerative) CIs are set forth. The specific features of patient management in relation to the etiology of CI, as well as the place of neurometabolic therapy in the treatment of these impairments are discussed.